2019
DOI: 10.1159/000499077
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs: A Potential Pharmacological Treatment for Intracranial Aneurysm

Abstract: Background: Saccular intracranial aneurysms (IAs) are outpouchings of the vessel wall of intracranial arteries. Rupture of IAs results in subarachnoid hemorrhage which is associated with high morbidity and mortality. Surgical interventions, such as clipping and coiling, have associated risks. Currently, there are no proven pharmacological treatments to prevent the growth or rupture of IAs. Infiltration of proinflammatory cytokines in response to increased wall sheer stress is a hallmark of IA. Nonsteroidal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 56 publications
(98 reference statements)
3
21
0
Order By: Relevance
“…Accordingly, in this study, the anti-inflammatory properties of neostigmine have shown a clear synergistic effect within 24 h when added to celecoxib (Neo + Cele), which then declined after 5 days of the study, an effect that is attributed to Neo rather than Cele. This outcome comes in accordance with the study of Nishyama 31 The positive feedback loop of the Cox-2-PGE 2 -EP 2 -NF-κB signaling pathway is well known to initiate and preserve inflammation (35). Activated Cox-2 increase the production of PGE 2 , that binds to the EP 2 receptor and consequently activates NF-κB; the important inducer of pro-inflammatory cytokine (35,36).…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, in this study, the anti-inflammatory properties of neostigmine have shown a clear synergistic effect within 24 h when added to celecoxib (Neo + Cele), which then declined after 5 days of the study, an effect that is attributed to Neo rather than Cele. This outcome comes in accordance with the study of Nishyama 31 The positive feedback loop of the Cox-2-PGE 2 -EP 2 -NF-κB signaling pathway is well known to initiate and preserve inflammation (35). Activated Cox-2 increase the production of PGE 2 , that binds to the EP 2 receptor and consequently activates NF-κB; the important inducer of pro-inflammatory cytokine (35,36).…”
Section: Discussionsupporting
confidence: 85%
“…Here, they undergo further differentiation and synthesize the inflammatory cytokines and immunoglobulins, as well as activate the complement system. Moreover, vascular inflammation contributes to the alteration of the endothelial function, disruption of the internal elastic lamina and collagen matrix, vasa vasorum activation and proliferation (6,8). Therefore, inflammation promotes other pathophysiologic mechanisms involved in IA formation like oxidative stress, cell adhesion, intraluminal thrombosis and apoptosis, which in turn, facilitate vascular inflammation leading to a kind of vicious circle (6,8,9).…”
Section: Functional Pathways Contributing To Ia Formationmentioning
confidence: 99%
“…Moreover, vascular inflammation contributes to the alteration of the endothelial function, disruption of the internal elastic lamina and collagen matrix, vasa vasorum activation and proliferation (6,8). Therefore, inflammation promotes other pathophysiologic mechanisms involved in IA formation like oxidative stress, cell adhesion, intraluminal thrombosis and apoptosis, which in turn, facilitate vascular inflammation leading to a kind of vicious circle (6,8,9). In summary, these processes prompt irreversible anatomical remodeling and functional alteration of the damaged vessel, eventually resulting in IA rupture (1).…”
Section: Functional Pathways Contributing To Ia Formationmentioning
confidence: 99%
“…Expanding to the previous ndings, a mouse model of Saccular Intracranial Aneurysms has shown that endothelia cells-activated NF-κB activity was suppressed with the administration of the selective Cox-2 inhibitor celecoxib (41). Moreover, the results of the Cox isoforms activity study in the present work come in accordance with a previous work from Nishiyama et al (45), where intrathecal administration of celecoxib resulted in a dose dependent inhibition of the inch response of the formalin test, but had no signi cant effect on the tail ick latency.…”
Section: Discussionmentioning
confidence: 66%
“…The positive feedback loop of the Cox-2-PGE 2 -EP 2 -NF-κB signaling pathway is well known to initiate and preserve in ammation (41). Activated Cox-2 increase the production of PGE 2 , that binds to the EP 2 receptor and consequently activates NF-κB; the important inducer of pro-in ammatory cytokine (41,42). More than twenty-ve cytokines are controlled directly by NF-κB.…”
Section: Discussionmentioning
confidence: 99%